Intellectual disability in the twentieth century : transnational perspectives on people, policy and practice / edited by Jan Walmsley and Simon Jarrett. - Walmsley, Jan; Jarrett, Simon (Policy Press, 2019)
Bringing together accounts of how intellectual disability was viewed, managed and experienced in countries across the globe, the book examines the origins and nature of contemporary attitudes, policy and practice, and sheds light on the challenges of implementing the UN Convention on the Rights of Persons with Disabilities (UNCPRD).